Academic Supervision in Improving Teacher Performance at MTs NU Banat Kudus (Educational Management, 2022)
The purpose of this study is to determine model and approach that is used in supervision, supervision techniques and stages of implementation of academic supervision. This study used qualitative method. The collected data used interviews, observation and documentation. The data analysis technique used flow model analysis technique. The result showed that (1) the model used scientific and the approach used a collaborative, (2) there were two kinds of supervision techniques, individual supervision techniques and group supervision techniques. Individual supervision with class visits, class observations and individual meetings. Group supervision techniques by holding coordination meetings and conducting training, and (3) the stages of implementation for supervision consist of planning, implementation, evaluation and follow up.